Evaluation of the Different Degrees of Thermal Stress in the Southern Coast of Iran - Mohammad Baaghideh; Alireza Entezari; Faezeh Shoji (جغرافیا و پایداری محیط)
Thermal stress is an important bioclimatic characteristic ofthe southern coast of Iran. This phenomenon which occurs due to the simultaneous increase in daily humid and temperature disrupts The body's normal activities and causes us considerable discomfort. The main injuries of thermal stress are muscle cramp, heat-stroke and fatigue. The current study, using heat index, aims to determine the impacts of temperature and humid on human discomfort .For this purpose, daily data regarding meteorological parameters were obtained from 14 stations in southern coast of Iran during the (1994-2008) period. The results which were prepared in the form of statistical analysis, suggest that different levels of heat intensity influences the climate of Southern coasts throughout the year, But intensity indices are maximized in August. Among the selected stations, Deylam port was recognized as sultriest station. The intensity of heat stress in the stations that located in the Persian Gulf coast was assessed generally greater than the coasts of the Oman sea.